Outcome of Laparoscopic Versus Open Appendicectomy: An Experience from BIRDEM General Hospital - Talukder, Md Rajibul Haque; Alam, Hasina; Alam, Md Noor A; Anwar, Raihan; Iqbal, Md Roushan; Chowdhury, Humayun Kabir (BIRDEM Medical Journal, 2016)
Aims: The aims of the study were to compare the safety and benefits of laparoscopic versus open appendicectomy. Methods: This cross-sectional study was done in BIRDEM General Hospital from June 2005 to December 2006.Seventy patients with acute appendicitis were included in this study, half underwent laparoscopic procedure and half open conventional procedure.We evaluated the length of hospitalization, postoperative morbidity (pain, wound infection, chest complication, paralytic ileus),cosmesis and return to normal activity among two methods of operations. Results: The duration of surgery in open group was 30 to 70 minutes with a mean duration of 47.57 minutes. In case of laparoscopic group the mean duration was 38.71 minutes with a range from 30 to 60 minutes. In open group 28 cases (80.0%) required opioid for satisfactory pain relief whereas in laparoscopic group only 9 (25.71%) cases required opioid. Gross infection with pus collection occurred in 2 (5.7%) cases in open appendicectomy (OA) group and none inlaparoscopic appendicectomy (LA) group. Post-operative hospital stay in open group ranged from 2 to 18 days with a mean of 6.74 days. For laparoscopic group the duration was 1 to 5 days with a mean of 2.31 days. Patients in open procedure returned to normal activity within 11-23 days with a mean of 15 days and in lap group the figures were 2-15 days and 6 days respectively. In open group 65.71% (n=23) were satisfied with the scar they had whereas 91.4% (n=32) were satisfied with their scar in lap group. Conclusion: The study indicates that the laparoscopic appendicectomy is feasible and safe for majority of patients with acute appendicitis. Birdem Med J 2015; 5(1) Supplement: 13-17